PEDAGOGICAL FOUNDATIONS FOR SUPPORTING CHILDREN WITH VARIOUS LEVELS OF INTELLECTUAL DEVELOPMENTAL DISABILITIES (World Bulletin of Education and Learning, 2025)
This article examines the pedagogical foundations for supporting children with various levels of intellectual developmental disabilities within contemporary special education systems. The study analyzes the conceptual, psychological, and methodological principles that guide inclusive and remedial education, highlighting how differentiated instruction, individualized learning plans, and adaptive teaching strategies contribute to the cognitive, social, and emotional development of these children. The research emphasizes the importance of early identification, functional assessment, interdisciplinary collaboration, and family involvement in designing effective support mechanisms. Special attention is given to the use of assistive technologies, therapeutic interventions, and structured learning environments that enhance children’s learning engagement and independence. The findings show that a comprehensive pedagogical framework, grounded in evidence-based practices and person-centered approaches, significantly improves the developmental potential, academic participation, and social integration of children with intellectual disabilities.
Keywords: Intellectual developmental disabilities, special education, differentiated instruction, individualized support, inclusive pedagogy, assistive technology, cognitive development, functional assessment, therapeutic intervention, adaptive learning.